TISSUE ATTACHMENT ON HYDROXYAPATITE COATED POLYMER-CERAMIC COMPOSITE IMPLANT - S. BAG; S. PAL; B. K. BISWAS; S. N. CHAKRABOTY (International Journal of Pharma and Bio Sciences, 2013)
Bioactive hydroxyapatite is regularly used as a thin bioactive coating layer over metallic implants to enhance the fixation between implants and bone. Experiment reveals that hydroxyapatite is not only improves the bone formation but also influence the soft tissue attachment over the implants. Hydroxyapatite coated small strips were cut out, sterilized and implanted into the femoral muscle of Sprague Dawli rat for soft tissue attachment. For hard tissue attachment the coated strip was placed in a defect area of bone of a white New Zealand rabbits. After a specific period, the implants were retrieved along with the tissue and examined under scanning electron microscope to observe the new soft and hard tissue growth around the implant via bioactive coating. From the SEM study it was observed that the attachment and regeneration of soft and hard tissue on the coated surface of composite strip was perfectly normal.